Day 4 Thu, May 05, 2016 2016
DOI: 10.4043/26986-ms
|View full text |Cite
|
Sign up to set email alerts
|

Can Teamwork Enhance Safety?

Abstract: Teams today often integrate the unique expertise of members in order to achieve performance and safety goals not possible by individuals alone, while facing challenges of operating in complex, diverse, and dynamic environments. However, simply relying on team member's expertise is not enough to produce effective teams. The science of team effectiveness has much to offer in regards to our understanding of developing and maintaining effective teamwork and safe behaviors, cognitions and attitudes in complex situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Evidence suggests that teams working together make fewer mistakes than individuals working on their own (Lerner et al, ). (2) Although team structure facilitates interaction between team members, having a team‐based structure per se does not create expected professional team dynamics (Salas et al, ). A reason for students to interact with each other and with faculty was necessary.…”
Section: The Hybrid Histology Course At Tulane University School Of Mmentioning
confidence: 99%
“…Evidence suggests that teams working together make fewer mistakes than individuals working on their own (Lerner et al, ). (2) Although team structure facilitates interaction between team members, having a team‐based structure per se does not create expected professional team dynamics (Salas et al, ). A reason for students to interact with each other and with faculty was necessary.…”
Section: The Hybrid Histology Course At Tulane University School Of Mmentioning
confidence: 99%
“…Teams are regarded as the basic structure for managing projects and tasks within organizations (Okoronkwo, 2017). Hence, each team member must have the capabilities to engage in collaborative work for team effectiveness (Salas and Iwig, 2016). Teamwork is the connected thoughts, behaviors, and emotions members use to work towards shared goals and create team success and value (Lee et al , 2017).…”
mentioning
confidence: 99%
“…5 To these ends, we were guided by previous work that showed that a structured approach for ARs in TM would improve their medical knowledge, provide an opportunity for them to learn and discuss TM topics with nonanesthesiologists, develop better judgment regarding blood utilization, and improve the safety of transfusions. 6,7…”
Section: Introductionmentioning
confidence: 99%